2008
DOI: 10.1016/j.joca.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen-inducible Cre-recombination in articular chondrocytes of adult Col2a1-CreERT2 transgenic mice

Abstract: Our findings demonstrate that the Col2a1-CreER(T2) transgenic mouse model is a valuable tool to target genes specifically expressed in articular chondrocytes in a temporally controlled manner in adult mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…The Col2a1Cre and AcanCreER drivers also cause FOXO deletion in other cartilaginous structures such as in the articular cartilage of the synovial joints and the growth plates (Henry et al, 2009; Zhu, Chen, Lichtler, O'Keefe, & Chen, 2008). We have recently reported the knee articular cartilage phenotype in these mouse models and demonstrated that FOXO are critical mediators of chondrocyte homeostasis by regulating PRG4 expression and maintaining the integrity of the cartilage superficial zone (Matsuzaki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Col2a1Cre and AcanCreER drivers also cause FOXO deletion in other cartilaginous structures such as in the articular cartilage of the synovial joints and the growth plates (Henry et al, 2009; Zhu, Chen, Lichtler, O'Keefe, & Chen, 2008). We have recently reported the knee articular cartilage phenotype in these mouse models and demonstrated that FOXO are critical mediators of chondrocyte homeostasis by regulating PRG4 expression and maintaining the integrity of the cartilage superficial zone (Matsuzaki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Col2a1-CreERT2 transgenic mice were generated as described previously [21,22]. GR flox/flox transgenic mice were backcrossed to the C57BL/6 background for 10 generations as previously described [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was therefore to investigate the role of endogenous GCs in cartilage and bone developments in normal physiology, and during fracture healing. To address this aim, we generated tamoxifen-inducible cartilage-specific GR knockout mice (Col2a1-CreERT2; GR flox/flox ), which allow precise temporal control of GR deletion within chondrocytes [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, Smad3 knockout mice show progressive articular cartilage degradation resembling human OA [44]. In order to overcome embryonic lethality and redundancy, we generated chondrocyte-specific Tgfbr2 conditional knockout mice (Tgfbr2 cKO or Tgfbr2Col2CreER mice) in which deletion of the Tgfbr2 gene is mediated by Cre recombinase driven by the chondrocyte-specific Col2a1 promoter in a tamoxifen (TM)-inducible manner [45, 46]. These mice exhibit typical clinical features of OA, including cell cloning, chondrocyte hypertrophy, cartilage surface fibrillation, vertical clefts, and severe articular cartilage damage as well as the formation of chondrophytes and osteophytes [47].…”
Section: Molecular Mechanisms Related To Oa Pathogenesismentioning
confidence: 99%